1978
DOI: 10.21236/ada059221
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of End-to-End Encryption in Secure Computer Networks

Abstract: When U.S. Government drawings, spcifications. or other data are used for any p. nose other than a definitely related governr procurement eoperation, the government thereby incurs no responsibility not any obligation whatsoever; and tho fact that ths government may have formulated, furnished, or in any way supplied the said 4 drawings. spoecifications, or ether data is not to be regarded by implication or otherwise, as in any manner licensing the holder or any other person or corporamton, or conveying any right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 0 publications
0
51
0
Order By: Relevance
“…Cabuk et al [17] suggest the use of -similarity test for detecting [17,90] timing channel, which has a feature of creating clusters of similar IPDs at multiples of some time intervals. This and some other existing detection methods [11,38] targets only specific timing channels, or can not perform well for high variation of network traffic.…”
Section: Defence Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cabuk et al [17] suggest the use of -similarity test for detecting [17,90] timing channel, which has a feature of creating clusters of similar IPDs at multiples of some time intervals. This and some other existing detection methods [11,38] targets only specific timing channels, or can not perform well for high variation of network traffic.…”
Section: Defence Mechanismsmentioning
confidence: 99%
“…Experiments showed that several timing channels can be detected, like: [90] channel (with abnormal shape and regularity), [17] (with similar shape and abnormal regularity), [40] (with similar shape and regularity as normal traffic) and [104] (with similar shape and regularity as normal traffic).…”
Section: Defence Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The very first covert timing channels are based on having a sender either send or remain silent in specific time intervals in order to communicate covert message bits 1 and 0, respectively [18,11]. These schemes not only are limited by the need for accurate synchronization between the sender and the receiver, but also are easily detectable using statistical tests [3].…”
Section: Related Workmentioning
confidence: 99%
“…The possibility of encoding covert channels in the timing of packets (or frames) was identified early by Padlipsky et al [5]. However, all the timing channels proposed prior to Berk's work [6] were based on encoding in varying packet rates over time as opposed to encoding in IPG values directly.…”
Section: Related Workmentioning
confidence: 99%